Identification of hsa_circ_0001821 as a Novel Diagnostic Biomarker in Gastric Cancer via Comprehensive Circular RNA Profiling - Kong, Shan; Yang, Qian; Tang, Chenxue; Wang, Tianyi; Shen, Xianjuan; Ju, Shaoqing (Frontiers in Genetics, 2019)
Background: The morbidity and mortality of gastric cancer (GC) remain high worldwide. With the advent of human Genome Sequencing Project, circular RNAs (circRNAs) have attracted widespread attention in cancer research due to their stable ring structure. Our aim was to identify differentially expressed circRNAs in GC and explore their potential roles in GC diagnosis, treatment and prognostic prediction. Methods: Large-scale gene screening was performed in 3 pairs of GC tissues and adjacent non-cancerous tissues using high-throughput sequencing. The expression of hsa_circ_0001821 was detected in 80 pairs of tissue samples by quantitative real time-PCR (qRT-PCR). Stability of the ring structure of hsa_circ_0001821RNA was verified by exonuclease digestion assay, and its diagnostic value was evaluated by ROC analysis. In addition, the location of hsa_circ_0001821 in GC cells was detected by nucleoplasm separation assay. Results: A total of 25,303 circRNAs were identified, among which 2,007 circRNAs were differentially expressed (fold change >2.0, P<0.05). Further validation disclosed that hsa_circ_0001821 was significantly down-regulated in the 80 pairs of GC tissues and 30 whole blood specimens obtained from the GC patients. The specificity of hsa_circ_0001821 in GC was higher than that in other solid tumors. In addition, hsa_circ_0001821 was relatively stable after RNA exonuclease digestion. Clinicopathlogical parameter analysis showed that hsa_circ_0001821 was negatively correlated with tumor depth (r=-0.255, P=0.022) and lymph node metastasis (r=-0.235, P=0.036). Area under the curve (AUC) analysis showed that the diagnostic efficiency of circulating hsa_circ_0001821 in distinguishing GC patients was higher than that in GC tissues (0.872, 95%CI: 0.767-0.977 vs. 0.792, 95%CI: 0.723–0.861). Combined use of circulating hsa_circ_0001821 with the existing tumor markers yielded the largest AUC of 0.933. Finally, hsa_circ_0001821 was demonstrated to mainly locate in the cytoplasm, implying that it played a potential regulatory role in GC at the post-transcriptional level. Conclusion: Hsa_circ_0001821 may prove to be a new and promising potential biomarker for GC diagnosis.